The ‘japa’ syndrome of Nigerian youths as a survival strategy: A socio-economic perspective - Adeyamju, Faith; Alao, Bukola; Opakunbi, Oyedamade; Ajibade, Toluwalase (African Journal of Stability and Development (AJSD), 2024)
Nigeria is often referred to as the giant of Africa; still, it has over the last two years experienced an alarming surge in the migration of young Nigerians to other developed states. Factors such as the chronic unemployment rate, which stands at 33.3% as of 2020, high levels of insecurity, and unfulfilled aspirations have caused increased pressure in the search for better opportunities abroad. More interestingly, the increased migration rate most likely has nothing to do with the idolisation of these states, but rather is largely due to a lack of national development and economic growth, as youths have been found to migrate to countries with better economies within Africa. Although no accurate data exists on the rate of migration, this circumstantial migration reflects the continued struggle of citizens to improve their living conditions. The sudden increase in the international migration of young Nigerians is a critical issue that has not received much attention from the Nigerian government, especially in tackling the root causes and ways to further reduce its negative effects on the socio-economic development of the nation. Given these concerns, this study aims to further explore the push and pull factors influencing the migration of Nigerian youths and their patterns. More importantly, it examines the socio-economic implications of an increase in the migration rate in Nigeria. The findings of the study will be useful for an in-depth reality check and will serve as a wake-up call for the Nigerian government.